2023
DOI: 10.1021/acsanm.3c02636
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt/Cobalt Oxide Nanorods-Decorated Reduced Graphene Oxide (Co/Co3O4-rGO) for Enhanced Electrooxidation of Glycerol

Vijay S. Sapner,
Pratiksha D. Tanwade,
Ajay V. Munde
et al.

Abstract: Reduced graphene oxide with cobalt/cobalt oxide (Co/Co 3 O 4 -rGO) nanorod decorations was made by using a chemical synthesis process. The as-synthesized Co/Co 3 O 4 -rGO, reduced graphene oxide (rGO), and cobalt/cobalt oxide (Co/Co 3 O 4 ) nanocomposite were tested for electrocatalytic activity toward the electrooxidation of glycerol in 1 M KOH solution and oxygen evolution reaction simultaneously. The as-synthesized electrocatalytic system was characterized by various techniques, including electrochemical (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Oh et al demonstrated the effect of nanostructuring of the Au catalyst and the local KOH concentration on GLYOR . Many earth-abundant catalysts have been reported for GLYOR with high formic acid selectivity. , A cobalt oxide nanorod decorated on reduced graphene oxide (RGO) is effective for GLYOR with high formate selectivity; however, the high selectivity of formic acid production required a longer reaction time and a high potential . Other strategies, such as defect creation on the electrocatalyst surface, are also suggested to boost the GLYOR performance .…”
Section: Introductionmentioning
confidence: 99%
“…Oh et al demonstrated the effect of nanostructuring of the Au catalyst and the local KOH concentration on GLYOR . Many earth-abundant catalysts have been reported for GLYOR with high formic acid selectivity. , A cobalt oxide nanorod decorated on reduced graphene oxide (RGO) is effective for GLYOR with high formate selectivity; however, the high selectivity of formic acid production required a longer reaction time and a high potential . Other strategies, such as defect creation on the electrocatalyst surface, are also suggested to boost the GLYOR performance .…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional graphene, containing a lattice of sp 2 carbons, has garnered much attention for its multiple applications in composite materials, energy storage devices, electrocatalysts, 1,2 sensors, 3 etc. 4–6 Additionally, extensive scientific and industrial research on the exfoliation of graphite/graphene into fewer sheets, is also being undertaken. 7–9 During exfoliation, the multiple layers of graphene, which are held together by weak van der Waals forces, are separated/moved apart, producing a 2D material that can be used for various applications such as in electronics, photonics, energy storage, composites, sensors etc .…”
mentioning
confidence: 99%